Did Polish Bishops Support Andrzej Duda in the Presidential Campaign in 2020? Analysis of Institutional Messages of the Polish Episcopal Conference - Leśniczak, Rafał (Political Preferences, 2020)
The aim of the article is to increase the cognitive value in the area of political communication of Polish bishops during the presidential campaign in Poland in 2020, in particular to answer the question whether the Polish Episcopal Conference supported President Andrzej Duda politically in his candidacy for re-election. The research applied the analysis and synthesis method supplemented with elements of hermeneutics. The Polish Episcopal Conference remained an entity not politically involved at the level of institutional communiqués and did not support any of the candidates applying for the office of President of the Republic of Poland in 2020. The issue for further political and media research remains that of complementary forms of communication of the ecclesial institution and the way of expressing one's own electoral preferences, for example through the Catholic media.